Editorial Information – Proceedings of the III Brazilian Symposium on Urban Waters - Américo-Pinheiro, Juliana Heloisa Pinê; Vanzela , Luiz Sérgio; Benini , Sandra Medina (Scientific Journal ANAP, 2025)
The III Brazilian Symposium on Urban Waters was held as part of the Special Edition of the Scientific Journal ANAP (v. 03, n. 14, 2025), bringing together researchers, professors, and partner institutions to address a highly relevant theme for urban sustainability: the planning and management of urban waters. The event was organized by the Friends of Nature Association of Alta Paulista (ANAP), in partnership with the Graduate Program in Environmental Sciences at Universidade Brasil and the Water Analysis Laboratory of the Faculty of Agronomic Sciences at UNESP (Botucatu). The organizing committee included Prof. Dr. Juliana Heloisa Pinê Américo-Pinheiro, Prof. Dr. Luiz Sérgio Vanzela, and Prof. Dr. Sandra Medina Benini, who coordinated both the event and the publication of the proceedings. The symposium gathered a broad scientific committee composed of faculty members and researchers from several Brazilian institutions, such as UNESP, UNIVAG, UNICENTRO, PUC Goiás, Mackenzie, and UNINOVE, among others, who evaluated and selected the works presented. The main objective was to promote theoretical and practical debates on the importance of planning and managing urban waters, integrating academic, technical, and social perspectives. Throughout the event, participants had the opportunity to share research, experiences, and proposals contributing to addressing challenges related to the quality, availability, and governance of water in urban contexts.